Pathogenic viruses incidence, severity and detection in lettuce, in the state of Queretaro, Mexico - Pérez Moreno, Luis; Niño Mendoza, Graciela Hortensia; Mendoza Celedón, Briseida; León Galván, Ma. Fabiola; Robles Hernández, Loreto; González Franco, Ana Cecilia (Acta Universitaria, 2016)
The present study evaluated incidence, severity, and viral frequency by means of ELISA of luteovirus, Beet western yellows virus (BWYV), Cucumovirus, cucumber mosaic virus (CMV), Potyvirus, lettuce mosaic virus (LMV), Alfamovirus, alfalfa mosaic virus (AMV), and tospovirus, Tomato spotted wilt virus (TSWV). Experimental randomized complete block design was used, with three replicate. Plus, a multiple comparison of means with Tukey P ≤ 0.05. Virus severity and incidence was different depending of the planting date and the locality. Second planting date, in Pedro Escobedo county, Qro., Mexico, presented the highest severity and incidence. BWYV, CMV, LMV, AMV and TSWV viruses were detected, at 9.8%, 23.6%, 0.9%, 2.2% and 9.3%, respectively.